UPAYA MENINGKATKAN DISIPLIN GURU DALAM KEHADIRAN MENGAJAR DI KELAS MELALUI PENERAPAN “REWARD AND PUNISHMENT” - li'ah haryati (MEDIA DIDAKTIKA, 2020)
The study aimed to find the alternative solutions in order to improve the discipline in the presence and leave of teachers in the classroom through the impelemtation of Reward and Punishment. This action research conducted to the teachers at the state elementary school of Maor, Kembangbahu , Lamongan in the first semester in the academic year of 2016/2017. The design of the study was a research design schools plot action, namely making cycle of an action plan, implementing action, observation and reflection of the implementation of the action during the two cycles. The results of these reflections were used as a guide for decision making a decision to continue or discontinue the study. The study was conducted a spiral in cycles until the second cycle. The results showed that the performance of teachers increased after the action of the implementation of Reward and Punishment for two cycles. Such improvements included an increase in developing school programs, execute, make the administration, conducting evaluations until the discipline to go to the class, implementing the learning, assessing learning achievement, and carrying out the follow up assessments of students’ achievement.